2018
DOI: 10.3892/ol.2018.8027
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast activation protein in osteosarcoma cells promotes angiogenesis via AKT and ERK signaling pathways

Abstract: Abstract. Although it is established as a marker of cancer-associated fibroblasts, the expression of fibroblast activation protein (FAP) is not restricted to stromal cells; its expression in multiple types of tumor cell and its pro-tumor functions have been reported. However, the role of FAP in angiogenesis in osteosarcoma remains uncharacterized. In the present study, it was identified that the mRNA and protein expression levels of FAP and vascular endothelial growth factor-A (VEGF-A) corresponded to each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Since the discovery of FAP, early research focused mainly on its structure, distribution, and double enzymatic activity. However, recent studies have shown that FAP could be over-expressed on the surface of certain tumor cells (14,(28)(29)(30). Some studies found that the proliferation and migration capacity of tumor cells increased significantly after the lentiviral transfection of the FAP-overexpression plasmid, suggesting that FAP could serve as an oncogene and activate potential signaling pathways like PI3K and FAK (15,32,33), but results contradicting these findings have also been produced (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of FAP, early research focused mainly on its structure, distribution, and double enzymatic activity. However, recent studies have shown that FAP could be over-expressed on the surface of certain tumor cells (14,(28)(29)(30). Some studies found that the proliferation and migration capacity of tumor cells increased significantly after the lentiviral transfection of the FAP-overexpression plasmid, suggesting that FAP could serve as an oncogene and activate potential signaling pathways like PI3K and FAK (15,32,33), but results contradicting these findings have also been produced (15).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that the high expression of FAP in some tumors can often predict poor prognosis in malignancies like colorectal cancer (11), esophageal squamous cancer (12), and lung squamous cell carcinoma (13). However, FAP may also play a restraining role in other tumors (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The ERK and phosphoinositide 3-kinase/AKT signaling pathways serve an important role in a multitude of cellular functions, including cell proliferation (21), survival (22), migration (23), apoptosis (24,25) and angiogenesis (15). However, whether ERK or AKT can function as downstream targets of Rab23 remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ab150077; 1:4,000; Abcam) at room temperature for 1.5 h. Signals on the membrane were detected using ECL reagents (Pierce; Thermo Fisher Scientific, Inc., Waltham, MA, USA). The results were quantified using Image-Pro software (version 5.1; Media Cybernetics, Inc., Rockville, MA, USA) (15).…”
Section: Methodsmentioning
confidence: 99%
“…Modulation of TIMP3, MMP1, MMP3, MMP11 have been shown to influence in vitro invasiveness of OS cells, and enhance in vivo tumorigenicity (34)(35)(36). OS cell interactions with local stromal cells such as mesenchymal stem cells (37) and endothelial cells (38,39), have been found to be pro-tumorigenic, whereas interactions with natural killer cells (40) or primed dendritic cells (41), were shown to have anti-tumor effects.…”
Section: Biology Of Pulmonary Metastases Dissemination From the Primamentioning
confidence: 99%